Climate Change Impacts on Rural Poverty in Low-Elevation Coastal Zones - Barbier, Edward B. (World Bank, Washington, DC, 2015)
This paper identifies the low-elevation coastal zone populations and developing regions most vulnerable to sea-level rise and other coastal hazards, such as storm surges, coastal erosion, and salt-water intrusion. The focus is on the rural poor in the low-elevation coastal zone, as their economic livelihoods are especially endangered directly by coastal hazards and indirectly through the impacts of climate change on key coastal and near-shore ecosystems. Using geo-spatially referenced malnutrition and infant mortality data for 2000 as a proxy for poverty, this study finds that just 15 developing countries contain over 90 percent of the world’s low-elevation coastal zone rural poor. Low-income countries as a group have the highest incidence of poverty, which declines somewhat for lower-middle-income countries, and then is much lower for upper-middle-income economies. South Asia, East Asia and the Pacific, and Sub-Saharan Africa account for most of the world’s low-elevation coastal zone rural poor, and have a high incidence of poverty among their rural low-elevation coastal zone populations. Although fostering growth, especially in coastal areas, may reduce rural poverty in the low-elevation coastal zone, additional policy actions will be required to protect vulnerable communities from disasters, to conserve and restore key coastal and near-shore ecosystems, and to promote key infrastructure investments and coastal community response capability.